Hal-Hal yang ada Hubungan dengan Gagal Jantung pada Penderita di Beberapa Lokasi Di Wilayah Asia, Amerika, dan Eropa Periode Tahun 2001 Sampai dengan Tahun 2021 - Nurani, Putri; Madjid, Baedah; Sartika, Suriana Dwi (Fakultas Kedokteran Universitas Bosowa, 2023)
Heart failure is a condition of abnormalities in the function and structure of the heart that results in the heart not being able to pump blood throughout the body adequately to meet the metabolic needs of tissues, or the heart can pump blood if the filling pressure of the heart is very high.To find out things that have a relationship with heart failure in patients in several locations in Asia, America, and Europe for the period 2001 to 2021.The research method used is a systematic review by synthesizing the results obtained by eight scientific research journals with a case control research design. Data from eight research results analyzed showed that there was a significant relationship between nutritional status, hypertension, smoking habits, and physical activity (p value < 0.05%) with heart failure in patients in several locations in Asia, America, and Europe in 2001. until 2021. Meanwhile, there is no significant relationship between diabetes mellitus (p value > 0.05%) and heart failure in patients in several locations in Asia, America, and Europe from 2001 to 2021. Heart failure in patients in several locations in Asia, America, and Europe from 2001 to 2021 had a significant relationship with nutritional status, hypertension, smoking habits, and physical activity, and no relationship with diabetes mellitus.